Handgrip strength as a predictor of bone mineral density in cirrhotic outpatients - Santos, Lívia Alves Amaral [UNESP]; Lima, Talles Bazeia [UNESP]; Augusti, Laís [UNESP]; de Campos Franzoni, Letícia [UNESP]; da Silva Yamashiro, Fabio [UNESP]; Bolfi, Fernanda [UNESP]; Nunes, Vânia dos Santos[UNESP]; Dorna, Mariana de Souza [UNESP]; Oliveira, Cássio Vieira de[UNESP]; Caramori, Carlos Antonio [UNESP]; Silva, Giovanni Faria [UNESP]; Romeiro, Fernando Gomes [UNESP] (Wiley, 2015)
Osteoporosis is well recognized as a cirrhosis complication; however, most studies assessing this condition included only patients on liver transplantation lists with an elevated rate of bone diseases. While general population studies show that handgrip strength is clearly associated with bone mineral density, until now this tool has not been applied to cirrhotic patients in relation to their bone condition. This study aimed to evaluate whether handgrip strength, bone and liver tests may be useful as predictors of bone disease in cirrhotic outpatients. 129 subjects were included (77 men and 52 women). Dual energy X-ray absorptiometry was applied to evaluate lumbar-spine and femoral-neck T scores. Osteoporosis/osteopenia rates were 26.3%/35.6% in the lumbar spine and 6.9%/41.8% in the femoral neck, respectively. Model selections were based on backward procedures to find the best predictors of low T scores. For lumbar spine, only low handgrip strength and high parathyroid hormone levels were clearly related to low T scores. For femoral neck, only age was associated with low T scores. Handgrip strength may serve as an effective predictor of low lumbar spine T score among cirrhotic outpatients. As cirrhosis affects the lumbar spine more than the femoral neck, these results suggest that handgrip strength should be tested in all cirrhotic patients as a first indicator of bone health. This article is protected by copyright. All rights reserved.
Keywords: Handgrip strength; Liver cirrhosis; Osteopenia; Osteoporosis